(untitled) (GYMNASIUM, 2009)
ICT stands for the English: “Information and Communication Technologies”, and its French equivalent is TIC, meaning: “Technologies de l’Information et de la Communication”. Thus explaining that in the Romanian language, the usage of both collocations is permitted, depending on the speaker, if he is either English-speaking or Francophone. In any case, both options are viable and stand for “Information and Communication Technologies”, about which a lot of dictionaries, including “Techencyclopedia” says “it is the umbrella term that covers the whole of the computer technology”, generally referred to as IT (Information Technology).